Diazotrophs for Lowering Nitrogen Pollution Crises: Looking Deep Into the Roots - Imran, Asma; Hakim, Sughra; Tariq, Mohsin; Nawaz, Muhammad Shoib; Laraib, Iqra; Gulzar, Umaira; Hanif, Muhammad Kashif; Siddique, Muhammad Jawad; Hayat, Mahnoor; Fraz, Ahmad; Ahmad, Muhammad (Frontiers in Microbiology, 2021)
During and after the green revolution in the last century, agrochemicals especially nitrogen (N) were extensively used. However, it resulted in a remarkable increase in crop yield but drastically reduced soil fertility; increased the production cost, food prices, and carbon footprints; and depleted the fossil reserves with huge penalties to the environment and ecological sustainability. The groundwater, rivers, and oceans are loaded with N excess which is an environmental catastrophe. Nitrogen emissions (e.g., ammonia, nitrogen oxide, nitrous oxide) play an important role in global climate change and contribute to particulate matter and acid rain causing respiratory problems, cancers, and damage to forests and buildings. Therefore, the nitrogen-polluted planet Earth needs concerted global efforts to avoid the disaster. Improved agricultural N management focuses on the synchronization of crop N demand and N supply along with improving the N-use efficiency of the crops. However, there is very little focus on the natural sources of N available for plants in the form of diazotrophic bacteria present inside or on the root surface and the rhizosphere. These diazotrophs are the mini-nitrogen factories that convert available (78%) atmospheric N2 to ammonia through a process known as “biological nitrogen fixation” which is then taken up by the plants for its metabolic functioning. Diazotrophs also stimulate root architecture by producing plant hormones and hence improve the plant’s overall ability to uptake nutrients and water. In recent years, nanotechnology has revolutionized the whole agri-industry by introducing nano-fertilizers and coated/slow-releasing fertilizers. With this in mind, we tried to explore the following questions: To what extent can the crop N requirements be met by diazotroph inoculation? Can N input to agriculture be managed in a way leading to environmental benefits and farmers saving money? Can nanotechnology help in technological advancement of diazotroph application? The review suggests that an integrated technology based on slow-releasing nano-fertilizer combined with diazotrophs should be adopted to decrease nitrogen inputs to the agricultural system. This integrated technology would minimize N pollution and N losses to much extent.